DIGITAL MARKETING STRATEGIES AND ELECTRONIC WORD-OF-MOUTH IN ENHANCING MARKETING PERFORMANCE: EVIDENCE FROM MANANI SHOP - Mubarok, Alvin Athilla; Prihadi , Deddy; Wicaksono , Siddik Erdi (Penerbit Lafadz Jaya, 2025)
This study aims to analyze the influence of digital marketing strategies and word of mouth on marketing performance at Manani Shop, a thrift fashion MSME in Tegal City. Facing increasingly fierce business competition and shifting consumer behavior toward digital media, utilizing digital marketing strategies and the power of word of mouth (WOM) is crucial for increasing competitiveness and customer loyalty. This study employed a quantitative approach, using a survey method with 120 respondents who were active Manani Shop customers. The analysis techniques used included validity and reliability tests, and multiple linear regression. The results showed that both digital marketing strategies and word of mouth, both partially and simultaneously, had a positive and significant impact on marketing performance. Effective digital marketing strategies through social media platforms such as Instagram and TikTok have been shown to increase brand awareness and customer interaction. Meanwhile, word of mouth, particularly in the form of electronic word of mouth (e-WOM), plays a crucial role in building trust and driving purchasing decisions. These findings provide theoretical and practical implications for MSMEs in designing more adaptive and sustainable marketing strategies in the digital era.